Determinants of Auditor Switching in Infrastructure Companies Listed on the Indonesia Stock Exchange (IDX) for the 2019–2023 Period - Ramdani, Devinda; Putra, Rudi Syaf; Fionasari, Dwi (Jurnal Manajemen Perbankan Keuangan Nitro, 2026)
This study aims to investigate the influence of audit opinion, audit fee, management change, and financial distress on auditor switching among infrastructure sector companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2023 period. Auditor switching is understood as a company’s decision to replace its Public Accounting Firm (KAP), either as a consequence of regulatory requirements or as a voluntary managerial decision intended to maintain auditor independence and ensure the objectivity of the financial statement audit process. The inconsistencies found in previous empirical studies regarding the determinants of auditor switching provide a strong rationale for conducting further research, particularly within the infrastructure sector, which is characterized by complex operational activities and is subject to relatively high levels of regulatory oversight. The sample was selected using a purposive sampling technique, resulting in 30 companies with a total of 150 observations over the study period. This research employs a quantitative approach utilizing analytical methods that include descriptive statistics, logistic regression analysis, and hypothesis testing through the Wald test. The results indicate that audit opinion and audit fee do not have a significant effect on auditor switching. Conversely, management change is found to have a positive and significant influence on auditor switching, while financial distress does not exhibit a significant effect. Overall, management change is identified as the most dominant factor influencing auditor switching.